2002
DOI: 10.1002/jclp.2011
|View full text |Cite
|
Sign up to set email alerts
|

Patterns of substance use in treatment‐seeking problem gamblers: Impact on treatment outcomes

Abstract: Accumulating evidence suggests that treatment-seeking problem gamblers have high rates of substance abuse. However, relatively little is known about the relation between gambling problems and specific psychoactive substances apart from alcohol and methadone-treated opiate addicts. In this study of 169 individuals seeking outpatient treatment for problem gambling, lifetime drug use and medication use were very high. Approximately half of the sample were using a psychiatric medication at the time they sought gam… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

3
33
1

Year Published

2005
2005
2022
2022

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 34 publications
(37 citation statements)
references
References 9 publications
3
33
1
Order By: Relevance
“…This was low in comparison to Toneatto et al's study in Canada, where the incidence was 10.1 % and to Abait's study in Argentina, where the incidence was 12.6 % (Toneatto et al 2002;Abait and Folino 2007). The result was, however, in keeping with a recent Spanish study by Echeburua et al (2013) where they found that alcohol abuse was not higher among pathological gamblers when compared to non-gamblers.…”
Section: Alcohol and Substance Use Disorderscontrasting
confidence: 68%
See 1 more Smart Citation
“…This was low in comparison to Toneatto et al's study in Canada, where the incidence was 10.1 % and to Abait's study in Argentina, where the incidence was 12.6 % (Toneatto et al 2002;Abait and Folino 2007). The result was, however, in keeping with a recent Spanish study by Echeburua et al (2013) where they found that alcohol abuse was not higher among pathological gamblers when compared to non-gamblers.…”
Section: Alcohol and Substance Use Disorderscontrasting
confidence: 68%
“…A positive association was also detected between a history of psychiatric disorders and current comorbidity with substance-use disorders, as well as between alcohol abuse and age. Toneatto et al (2002) studied a group of 169 Canadian Gamblers and reported that 10.1 % were using drugs the month before treatment. A considerable number of these gamblers had sought treatment for their alcohol and drug use before seeking treatment for gambling problems.…”
Section: Introductionmentioning
confidence: 98%
“…The literature suggests that higher rates of alcohol use are present among pathological gamblers as compared to the general population (Cunningham-Williams et al, 1998;Maccallum and Blaszczynski, 2002;Toneatto et al, 2002), problem gambling is more common among individuals with alcohol use disorders as compared to those without such disorders (Grant et al, 2002), alcohol use is a risk factor for pathological gambling (Welte et al, 2004b), and gambling and excessive alcohol consumption are co-occurring activities (Elia and Jacobs, 1993).…”
Section: Introductionmentioning
confidence: 99%
“…Four studies assessed substance use disorders, mostly alcohol (Toneatto et al, 2002;Stinchfield, Kushner, & Winters, 2005;Hodgins, Peden, & Cassidy, 2005;Echeburua et al, 1996). Two studies (Leblond, Ladouceur, & Blaszczynski, 2003;Echeburua et al, 1996) assessed a personality variable and found an effect on treatment.…”
Section: Resultsmentioning
confidence: 98%
“…The studies include Canada (Toneatto, Skinner, & Dragonetti, 2002), Australia (Blaszczynski & Steel, 1998;Maccallum & Blaszczynski, 2002), Brazil (de Carvalho, Collakis, de Oliveira, & da Silveira, 2005, Israel (Dannon et al, 2004), Germany (Knecht, 1993), France (Lejoyeux, Feuche, Loi, Solomon, & Ades, 1999), Lithuania (Skokauskas, Satkeviciute, & Burba, 2003), and Spain (Ibanez et al, 2001).…”
Section: Co-occurring Disorders Among Problem Gamblersmentioning
confidence: 98%